How big is the crowding-out effect of user fees in the rural areas of Ethiopia?: implications for equity and resource mobilization - Asfaw, Abay; von Braun, Joachim (2004)
Using a nested multinomial logit model, this study investigates the demand “reduction” and “diversion” effects of user fees in rural areas of Ethiopia. The results reveal that an increase in user fees of public clinics, which are the most widely used alternative, can have a significant demand reduction effect on the poorest of the poor. This implies that despite cost recovery has been advocated as an alternative means of health care financing in most of the developing world, increasing user fees may drive the poorest segment of the population out of the health care market unless some protective measures are taken. -- from Article